1986
DOI: 10.3109/00016348609158221
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Somatopsychic Reactions in Vulvectomy‐Operated Women and their Partners

Abstract: Sexual function and somatopsychic reactions were examined in 25 women following vulvectomy and in 15 of their partners. More than half of the women had both sexual dysfunction and psychological problems. Their partners had no sexual dysfunction but almost half had psychological problems. An important reason for this seems to be insufficient information and advice both pre- and postoperatively and failure to recognize a developing stricture of the introitus vaginae. Frequent control and advice to both partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 8 publications
0
42
1
2
Order By: Relevance
“…The main focus of the studies available on vulvar cancer and psychosocial well-being/quality of life is sexual functioning; this domain of quality of life appears to be significantly reduced in vulvar cancer patients [20][21][22][23][24]. Apart from our present study the only other study on vulvar cancer and global quality of life was performed by Janda et al They developed a vulvar cancer-specific quality of life subscale to accompany the Functional Assessment of Cancer-General (FACT-G) questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of the studies available on vulvar cancer and psychosocial well-being/quality of life is sexual functioning; this domain of quality of life appears to be significantly reduced in vulvar cancer patients [20][21][22][23][24]. Apart from our present study the only other study on vulvar cancer and global quality of life was performed by Janda et al They developed a vulvar cancer-specific quality of life subscale to accompany the Functional Assessment of Cancer-General (FACT-G) questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…For some women, sexuality has been shown to be adversely affected by the surgery, including a reported decreased frequency of sexual intercourse (Corney et al 1992), decreased desire and arousal (Andreasson et al 1986) and an increased prevalence of sexual dysfunction compared with healthy women (Andersen & Hacker 1983, Stellman et al 1984, Likes et al 2007, Hazewinkel et al 2012. It is also evident that for some women, intimacy and relationship status are more closely linked to sexual satisfaction than physical arousal (Weijmar Schultz et al 1986, Willibrord et al 1990.…”
Section: Introductionmentioning
confidence: 99%
“…10 Extensive surgery, such as vulvectomy, can lead to abnormal anatomy and thereby cause impairment of self-image and sexual function. 11 Recently, in a pilot study, van Seters demonstrated the positive effects of treatment with imiquimod, a topical immune response modifier. 12 It was observed that in 30% of cases treatment with imiquimod led to complete remission of the lesions, while another 60% of patients showed a partial remission.…”
mentioning
confidence: 99%